2014
DOI: 10.1063/1.4874636
|View full text |Cite
|
Sign up to set email alerts
|

Inter-cage dynamics in structure I, II, and H fluoromethane hydrates as studied by NMR and molecular dynamics simulations

Abstract: Prospective industrial applications of clathrate hydrates as materials for gas separation require further knowledge of cavity distortion, cavity selectivity, and defects induction by guest-host interactions. The results presented in this contribution show that under certain temperature conditions the guest combination of CH 3 F and a large polar molecule induces defects on the clathrate hydrate framework that allow intercage guest dynamics.13 C NMR chemical shifts of a CH 3 F/CH 4 /TBME sH hydrate and a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(89 reference statements)
2
16
0
Order By: Relevance
“…Reported enhanced water dynamics in CH 3 Fh ydrates (sI, sII, and sH) are likely to be attributable to special host-guest interactions. [41] In other gas hydrate systems, hydrogen bondingc an occur between guest and host, for example, the 5 12 cage of CO 2 in sI CO 2 hydrates. It is reported that the 5 12 cage occupancyo fC O 2 hydrate is about 70 %o rh igher,w hich is greater than that expected for am olecule of this size (the maximum van der Waals diameter (and volume) of CO 2 is 5.…”
Section: Host-guestinteractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported enhanced water dynamics in CH 3 Fh ydrates (sI, sII, and sH) are likely to be attributable to special host-guest interactions. [41] In other gas hydrate systems, hydrogen bondingc an occur between guest and host, for example, the 5 12 cage of CO 2 in sI CO 2 hydrates. It is reported that the 5 12 cage occupancyo fC O 2 hydrate is about 70 %o rh igher,w hich is greater than that expected for am olecule of this size (the maximum van der Waals diameter (and volume) of CO 2 is 5.…”
Section: Host-guestinteractionsmentioning
confidence: 99%
“…One other effect of increased host–guest interactions, which are likely to result from hydrogen bonding, is the greater mobility of water molecules, as demonstrated by decreased activation energies for water reorientation. Reported enhanced water dynamics in CH 3 F hydrates (sI, sII, and sH) are likely to be attributable to special host–guest interactions …”
Section: Introductionmentioning
confidence: 99%
“…Henning et al studied the formation process of CO 2 hydrates from the deuterated ice at the pressure of 6.2 MPa by neutron diffraction. Trueba et al obtained a series of NMR spectra of various hydrates at temperature from 183 to 253 K. Similarly, a lot of experiments on the quantitative analysis of gas hydrates were conducted under extreme high pressure or extreme low temperature, deviated from the usual hydrate formation conditions of several MPa and degrees centigrade . In other words, the results of these researches may be different from actual conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous MD simulations reported that the relaxation time is affected by the occupancy of clathrate hydrates. 59,64 More detailed analysis focusing on the occupancy and types of guest molecules should be performed in future considering varying degrees of occupancy of the small cages.…”
Section: (C) the Hydrogen Bonded O-h Stretchingmentioning
confidence: 99%